Effect of treatment mode on microstructure evolution and mechanical properties of nickel-based superalloy fabricated by selective laser melting. (May 2022) - Hu, Tianyi; Sun, Rui; Li, Wei; Sakai, Tatsuo; Lashari, Muhammad Imran; Wang, Ping; Hamid, Usama
Abstract: Combined with scanning electron microscopy, transmission electron microscope, X-ray diffraction and electron backscatter diffraction, the effects of three treatment modes consisting of as-deposited, solid solution and solution aging state on mechanical structure-properties of a nickel-based superalloy fabricated by selective laser melting were studied. Grains have preferred orientation, i.e. strong texture along {100}. The phase transformation processes during post-heat treatments include dissolution of Laves phase, precipitation of strengthening phases γ′, γ′′ and δ, and size reduction of δ phase. Especially for solution aging treatment, the refined grains, high dislocation density and added high-angle grain boundaries cause a significant increase in strength and a decrease in ductility, which is consistent with the results of the tensile tests. The interior cracking behavior related to the micro-voids and microcracks formed by dislocation pile-ups and uncoordinated deformation around harder δ phase in a vacuum environment becomes a typical ductile failure mode. Graphical abstract: Image 1 Highlights: A microstructure evolution process with precipitation and reduction of δ phrase is proposed. Mechanical properties are affected by grain size, dislocation density and HAGBs. Interior ductile failure mechanism related to micro-voids and microcracks is elucidated.